ERA BARU LAYANAN PERPUSTAKAAN - Hariyah Hariyah (Perpustakaan Nasional RI, 2019)
Library services continue improving along with advances in information an communication technology. How do libraries face the digital era that straightly affects the type and quality of library services? This paper intended to show the condition of library services based on a study of three articles discussed in this paper. It is hoped that the study may increase the librarians knowledge and motivation so that they can provide the best services. As a result, librarians are expected to adapt to the changes in creative an innovative ways so that rhey can keep up with the users needs of information and consequently the users keep visiting the libraries.